2011
DOI: 10.1016/j.wear.2010.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive and impact wear of stone used to manufacture axes in Neolithic Greece

Abstract: Excavations at the Neolithic settlement at Makriyalos in Northern Greece brought to light a large number of stone axe heads, the majority of which were manufactured from serpentinite and igneous rocks. Detailed study of the manufacturing traces on the archaeological implements identified that both percussive (pecking) and abrasive techniques (sawing and grinding/polishing) were employed for the production of the axes. There is limited evidence, however, of how these processes may have been undertaken.The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Some researchers used basic kinematic structures for controlled guidance of lithic replicas in tasks like scraping (Tomenchuk, 1985), threshing (Anderson et al, 2006;Vargiolu et al, 2003) or milling (Dubreuil et al, 2015). Others used commercial pin on disk tribometers (Lewis et al, 2011), scratch testers (Astruc et al, 2003), or custom designed machines (Collins, 2008;Tomenchuk, 1985). Tomenchuk (1985) designed a basic electrically powered kinematic 'wear-tester' to perform linear scraping strokes with the specimen on exchangeable undergrounds.…”
Section: Robotic Data Generationmentioning
confidence: 99%
“…Some researchers used basic kinematic structures for controlled guidance of lithic replicas in tasks like scraping (Tomenchuk, 1985), threshing (Anderson et al, 2006;Vargiolu et al, 2003) or milling (Dubreuil et al, 2015). Others used commercial pin on disk tribometers (Lewis et al, 2011), scratch testers (Astruc et al, 2003), or custom designed machines (Collins, 2008;Tomenchuk, 1985). Tomenchuk (1985) designed a basic electrically powered kinematic 'wear-tester' to perform linear scraping strokes with the specimen on exchangeable undergrounds.…”
Section: Robotic Data Generationmentioning
confidence: 99%
“…As most experimental designs involve different variables and the first generation experiments seek the identification of major variables, these need to be tested individually in order to assess and evaluate their effect-causation and correlation with other variables in the experiment. Based on this evaluation, the second generation experiments often use mechanical or automated apparatuses which drastically reduces human variability, all the while controlling and manipulating system variables (Aldeias et al 2016;Dibble and Rezek 2009;Eren et al 2011;Iovita et al 2013;Key 2016;Magnani et al 2014;Schmidt et al 2019;Astruc et al 2003;Collins 2008Lewis et al 2011Pfleging et al 2019;Tomenchuk 1985;Calandra et al 2020).…”
Section: Second Generationmentioning
confidence: 99%
“…It has been suggested that a relatively hard lithology, such as quartz sandstone, along with water and ash for lubrication, could have been used in Ireland (Cooney & Mandal 1998, 13). Lewis et al (2011) have suggested the use of leather, an abrasive, probably sand, and a lubricant, such as animal fat and water.…”
Section: The Making Of the Hermitage Polished Stone Adzementioning
confidence: 99%